Cellulose Supported Pd(II) Complex Catalyzed Carbon-Carbon Bonds Formation - Sarkar, Shaheen M.; Rashid, S. S.; Karim, Kaykobad Md Rezaul; Siti Noor Hidayah, Mustapha; Yuen, Mei Lian; Normaiza, Z.; Khan, Maksudur R.; Rahman, Md. Lutfor (American Scientific Publishers, 2019)
Corn-cobs are an agro-industrial waste and composed of cellulose mostly. In this study cellulose was isolated from the waste corn-cobs and modified to polymeric hydroxamic acid palladium complex 1 and characterized by using a variety of spectroscopic methods such as field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma atomic emission spectroscopy (ICP-AES). The complex 1 exhibited high catalytic activity towards Suzuki and Heck coupling reactions of activated and deactivated aryl halides to give the respective coupling products with high yield. Moreover, the complex 1 was recovered and recycled five times with no considerable loss of catalytic overall performance.